Gastric Variceal Obliteration By Cyanoacrylate Glue Injection - Hussain, SMB; Hossain, MR; Rahman, MM; Parvin, S; Hossain, MD (Journal of Armed Forces Medical College, Bangladesh, 2012)
Introduction: Rupture Gastric varices (GVs) can lead to catastrophic gastrointestinal bleeding, though it is much less in number than that of rupture oesophageal varices (OVs). Successful haemostasis of such bleeding is difficult specially in the back ground of non availability of appropriate drugs and instruments. Case Report: Introduction of intra-variceal injection of cyanoacrylate glue since 1980s has changed the scenario, it is cheaper and effective in controlling GVs related bleeding. A case of successful control of gastric variceal bleeding is reported. DOI: http://dx.doi.org/10.3329/jafmc.v7i2.10397 JAFMC 2011; 7(2): 44-46